New perspectives in social studies on recreational running: The case of Poland - Stempień Jakub Ryszard; Mielczarek Rafał; Tokarski Jarosław (Sciendo, 2021)
The article concerns the phenomenon of the popularity of recreational running in Poland. A search of existing studies on this phenomenon shows a clear overrepresentation of survey studies (mostly self-completion questionnaires), which in practice narrows the scope of empirical findings to issues such as the structure of the population of amateur runners, runners' motivations, and running practices themselves. In contrast, there is limited recognition of the perspectives and experiences of the institutional actors who co-create the running boom. These actors are referred to as the stakeholders of the running boom in the article. In the second part of the text, we discuss the results of our own research, which focused on running competitions open to amateurs. Every year, several thousands of such events are organized in Poland. The study (standardized online desk research) was carried out on two randomly selected nationwide samples: N = 338 and N = 349 (measurements for 2014 and 2017). The research documented the activity of stakeholders of the running boom in the form of organization, sponsorship, and patronage of running events. However, it should be emphasized that certain activities are conducted by public sector entities (local governments); the involvement of market players is less visible. The conducted research also provides characteristics of the landscape of running events in Poland: their location (including regional distribution), size, and their most important sport features (distance and accompanying events). The time variable (2014 versus 2017) and the regional variable (Eastern Poland versus the rest of the country) were used as the basic independent variables in the statistical analyses. The study as a whole can be considered to be complementary to previous studies on the Polish running boom.